Trade Liberalization in Fund-Supported Programs - Sharer, Robert (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1998)
This study asseses trade liberalization in programs supported by the IMF by reviewing multiyear arrangements in the 1990s and six detailed case studies. It also discusses the main economic factors affecting trade policy targets.